Surgical Management of Symptomatic Extensor Digitorum Brevis Manus: A Proposed Algorithm for Treatment. Issue 10 (1st October 2015) - Waterman, Brian R.; Dunn, John C.; Kusnezov, Nicholas; Romano, David; Pirela-Cruz, Miguel A.
ABSTRACT: First described in 1734, the extensor digitorum brevis manus (EDBM) is an anomalous extensor muscle found in the dorsum of the wrist and hand. Extensor muscle variants of the hand are not uncommon, and EDBM has an estimated reported incidence of approximately 2%. Although few extensor muscle variants become clinically significant, there is a paucity of literature discussing these anatomic variants, with most reports arising from cadaveric studies or isolated case series. Similarly, there are few established indications for surgical treatment of EDBM. In this case report, we describe the successful treatment of a young patient with persistently symptomatic anomalous extensor tendon with surgical excision and propose an algorithm for management after failure of conservative measures.